Acquired epidermodysplasia verruciformis in a child with HIV infection. - Joshi, V.D.; Belgaumkar, V.A. (European Journal of Pediatric Dermatology, 2023)
Introduction. People with human immunodeficiency virus (HIV) infection portray a plethora of dermatoses including infectious, inflammatory, premalignant and malignant conditions. Seborrheic dermatitis is one such entity which is quite prevalent and can have grotesque presentation in HIV afflicted people. Many rashes mimic the clinical presentation of this dermatitis, including nutritional deficiencies and papulosquamous disorders amongst others. Pre-malignant entities like epidermodysplasia verruciformis, a rare condition resulting from persistent human papilloma virus (HPV) infection can manifest as corona seborrheica-like clinical picture. Hereby reported is a HIV seropositive male child, misdiagnosed as seborrheic dermatitis whose further evaluation unveiled epidermodysplasia verruciformis. Case report. A 12 year old HIV seropositive male presented with asymptomatic, non- scaly, skin-colored and hypopigmented lesions over scalp crossing the anterior hairline, with few discrete, flat keratotic papules on upper back. A high index of suspicion supported by subtle clinical clues such as the co-existence of non scaly, hypopigmented plaques and flat wart-like papules along with detection of characteristic HPV types in the lesions, led to the final diagnosis of epidermodysplasia verruciformis. Conclusion. Dermatoses in people living with HIV pose diagnostic challenges which the dermatologists can avert by greater awareness braced by adequate laboratory acumen to deal with such rare, potentially devastating disorders which masquerade as more common innocuous skin disorders.